The Influence of Islamic Preaching Content on Social Media on the Islamic Understanding of Generation Z - Alifa Nur Dzakiyyah; Alyaa Emita Sari; Alyssa Nurfauziah; Syafiq Akmal Fauzan; Tamara Khairunnisa Anjani; Windi Sri Hafsani; Edi Suresman (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the influence of Islamic da'wah content on social media on Generation Z's understanding of Islam. A descriptive quantitative method was used by distributing questionnaires to 76 respondents aged 18–22 years from several universities. Validity testing showed that all 15 items were valid, while the reliability test produced a Cronbach’s Alpha of 0.886, indicating excellent reliability. The findings reveal that Islamic da'wah content on social media positively affects understanding of faith, worship, and morality, and increases motivation to worship and improve daily behavior. However, respondents' ability to verify sources and religious references remains limited. Therefore, religious digital literacy should be strengthened so that Generation Z can use social media critically and gain a proper understanding of Islam.